Patterns of English Pronunciation Errors in Sebha Secondary Schools - Ahlam Ali Alhadi Lehmedi (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
English pronunciation remains a significant challenge for many Libyan learners, particularly in regions where exposure to native speech models is limited. This study investigates such challenges by focusing on common pronunciation error patterns in Sebha secondary schools. This study examines recurrent pronunciation errors among secondary school students in Sebha, Libya, with the aim of identifying their phonetic challenges and suggesting pedagogical solutions. Thirty students (ten from each of three secondary schools, male and female) were randomly selected to read a controlled list of ten words per target phoneme, and their productions were recorded for phonetic analysis. In addition, ten English teachers from the same schools completed structured questionnaires. Descriptive analysis revealed persistent difficulties with the consonants /ʤ/, /ʒ/, /θ/, /ð/, /tʃ/, /z/, /p/, and /v/, as well as the vowels /eɪ/, /aɪ/, /ɪə/, /ɜː/, /uː/, /iː/, /ʌ/, and /e/, particularly in contexts where multiple pronunciation variants occur. The dominant error type was sound substitution, largely attributable to first language interference, compounded by the orthographic system’s inconsistency between graphemes and phonemes, and the limited explicit focus on pronunciation in classroom practice. These findings suggest the need for systematic integration of pronunciation training into English language instruction, with emphasis on high-risk phonemes, awareness of orthographic influence, and contrastive analysis between English and learners’ first language. Such interventions could reduce fossilised errors, improve intelligibility, and enhance learners’ communicative competence in English.